Self Assistive Technology for Disabled People – Voice Controlled Wheel Chair and Home Automation System - R. Puviarasi; Mritha Ramalingam; Elanchezhian Chinnavan (Institute of Advanced Engineering and Science, 2014)
This paper describes the design of an innovative and low cost self-assistive technology that is used to facilitate the control of a wheelchair and home appliances by using advanced voice commands of the disabled people. This proposed system will provide an alternative to the physically challenged people with quadriplegics who is permanently unable to move their limbs (but who is able to speak and hear) and elderly people in controlling the motion of the wheelchair and home appliances using their voices to lead an independent, confident and enjoyable life. The performance of this microcontroller based and voice integrated design is evaluated in terms of accuracy and velocity in various environments. The results show that it could be part of an assistive technology for the disabled persons without any third person’s assistance.